Augmented myeloablative conditioning with thiotepa in acute myeloid leukemia – improved outcomes with similar toxicity. Issue 3 (23rd February 2019) - Sheth, Vipul; Nachmias, Boaz; Grisariu, Sigal; Avni, Batia; Or, Reuven; Shapira, Michael
Abstract: Myeloablative doses of busulfan (Bu) with fludarabine (Flu) have reduced toxicity, however, limited by an increased relapse rate. We aimed to improve outcome of Flu-Bu regimen by augmentation with thiotepa (TT) (10 mg/kg). Eighty-nine patients with AML, 44 patients conditioned with Flu-Bu (group 1), and 45 patients augmented with TT (Flu-Bu-TT, group 2), were retrospectively analyzed. Primary objectives were toxicity and outcomes. Major toxicities were comparable: mucositis ( p = 1.0), sepsis ( p = .7), severe venocclusive disease of liver (VOD) ( p = 1.0), and non-relapse mortality (NRM) (22 vs. 22%, p = .7). Five-year disease-free survival was significantly better in group 2 compared to group 1 (62 vs. 38%, p = .02). Five-year overall survival (OS) showed trend toward benefit in group 2 (62 vs. 42%, p = .06). Lower relapse rate in group 2 (14 vs. 46%, p = .005) contributed to better outcomes. Augmented regimen has better disease-free survival (DFS) (mainly due to reduced relapse rate) and similar toxicities as compared to Flu-Bu. Key points: Assessing the addition of TT to myeloablative conditioning (Flu, Bu) in patients undergoing allogeneic stem cell transplant for acute myeloid leukemia with regard to relapse rate, disease-free survival and toxicity. Addition of thiotepa improves disease-free survival and shows trend toward benefit in overall survival, by reducing relapses without additional toxicity.